A Case Report of X-Linked Hyperimmunoglobulin M Syndrome with Lipoma Arborescens of Knees. (12th October 2016) - Dong, Qiuting; Zhao, Jinxia; Yao, Zhongqiang; Liu, Xiangyuan; He, Huiying
Abstract : The X-linked hyperimmunoglobulin M syndrome (HIGM), caused by mutations in the CD40LG gene, is a kind of primary immunodeficiency disease (PID). Patients with X-linked HIGM are susceptible to infection as well as autoimmune diseases. Lipoma arborescens (LA) is a rare benign tumor, of which the pathogenesis mechanism has not been clearly understood. We report a case of HIGM combined with LA in a 22-year-old male patient. A new deletion mutation of CD40LG gene was detected in this case. The possible relationship between HIGM and LA was also discussed.